2016
DOI: 10.1098/rstb.2015.0544
|View full text |Cite
|
Sign up to set email alerts
|

Innovativeness as an emergent property: a new alignment of comparative and experimental research on animal innovation

Abstract: One contribution of 15 to a theme issue 'Innovation in animals and humans: understanding the origins and development of novel and creative behaviour'. Innovation and creativity are key defining features of human societies. As we face the global challenges of the twenty-first century, they are also facets upon which we must become increasingly reliant. But what makes Homo sapiens so innovative and where does our high innovation propensity come from? Comparative research on innovativeness in non-human animals al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 98 publications
(192 reference statements)
3
41
0
Order By: Relevance
“…This result is in accordance with the cautionary views that single problem-solving tests cannot be assumed to measure an overall (or any) cognitive capacity without studying the underlying mechanisms (Rowe and Healy 2014; Thornton et al 2014;Griffin 2016;Reader et al 2016), and with other findings that problem-solving performance can vary across task types and contexts (reviewed by Thornton and Lukas 2012). In our study, the inconsistency between tasks could have arisen from motivational differences, i.e., solving the obstacle-removal task was imperative to provision the chicks, whereas solving the food-acquisition task merely offered extra food items.…”
Section: Discussionsupporting
confidence: 88%
“…This result is in accordance with the cautionary views that single problem-solving tests cannot be assumed to measure an overall (or any) cognitive capacity without studying the underlying mechanisms (Rowe and Healy 2014; Thornton et al 2014;Griffin 2016;Reader et al 2016), and with other findings that problem-solving performance can vary across task types and contexts (reviewed by Thornton and Lukas 2012). In our study, the inconsistency between tasks could have arisen from motivational differences, i.e., solving the obstacle-removal task was imperative to provision the chicks, whereas solving the food-acquisition task merely offered extra food items.…”
Section: Discussionsupporting
confidence: 88%
“…A typical evoked-innovation study involves introducing a new problem to an individual, or, less often, to a group, allowing study of psychological processes, the adaptive consequences of innovation, and social transmission. The method also allows experimental manipulation of factors hypothesized to impact innovation, although this is still relatively uncommon in animal work at least [ 66 ]. In animal work and much research with children, the task often involves extraction of a reward from a puzzle.…”
Section: Approaches To the Study Of Innovationmentioning
confidence: 99%
“…[ 78 ] and commentaries thereon). Like studies of spontaneous innovation, there are measures to address such problems [ 79 ], and several additional measures are suggested in papers within this issue (see [ 18 , 37 , 66 , 80 ]). For example, presentation of a variety of tasks that differ in difficulty can ensure a reasonable number of solutions are observed and that the consistency of innovativeness across tasks and contexts is established.…”
Section: Approaches To the Study Of Innovationmentioning
confidence: 99%
See 1 more Smart Citation
“…Animal innovations (i.e. animals behaving in an innovative way) have been described in a number of taxa, particularly in resourcepoor or novel environments [64]. For example, Laland & Reader [65] found that fooddeprived guppies (Poecilia reticulata) are more likely to develop foraging innovations than non-food-deprived individuals.…”
Section: Behaviour Can Allow 'Forbidden' Interactionsmentioning
confidence: 99%